Study of the Mg-Nd alloy obtained by electrolysis in molten oxifluoride media - Soare V.; Burada M.; Ostvold T.; Kontoyannis C.; Stefanidaki E. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Mg-Nd alloys have been produced by electrolysis of the molten mixture LiF-NdF3-MgF2 using Nd2(CO3)3 and MgF2 as raw materials. An electrolysis cell was designed having the anode made of super dense graphite and the cathode made of molybdenum metal. The quasi-binary system (NdF3-LiF)eutectic-MgF2 was investigated and the liquidus line was determined using thermo-differential analysis. The solubility of Nd2(CO3)3 in the LiF-NdF3-MgF2 system was investigated by the carbothermal technique.